Reclaiming comprehensive public health - Loewenson, Rene; Accoe, Kirsten; Bajpai, Nitin; Buse, Kent; Deivanayagam, Thilagawathi Abi; London, Leslie; Méndez, Claudio A; Mirzoev, Tolib; Nelson, Erica; Parray, Ateeb Ahmad; Probandari, Ari; Sarriot, Eric; et al. (BMJ Journals, 2022)
This article was published in BMJ Global Health by BMJ Journals [© Author(s) (or their employer(s)) 2020. Re-use permitted under CC BY-NC. No commercial re-use. See rights and permissions. Published by BMJ.] and the definite version is available at: http://dx.doi.org/10.1136/bmjgh-2020-003886 The Journal's website is at: https://gh.bmj.com/content/5/9/e003886